TRAINING IN BREASTFEEDING AND COMPLEMENTERY FEEDING OF COMMUNITY HEALTH AGENTS FROM MACAÉ, RJ: RESULTS OF AN EXTENSION ACTION. (Fiep Bulletin - online, 2016)
Permanent Education in health's field is understood as continuous professional training to improve the quality of care, assistance and constant updating and improvement of health practices strategy. The study aims to present the results of the tests applied in training on infant feeding aimed to Community Health Agents (CHA) of Macaé. The teams PIBEX/UFRJ Iacol, PET Eacol and PET ESAURA, term 2012-2014, in partnership with the area of ??Continuing Education in Health, Coordination Strategies for Family Health Macaé, conducted a short course of infant feeding (IF) educational and health activities, in July 2014 to train new CHA Primary Care. Before and after school, scholars applied a pre and post-test self-filled, containing 5 objective questions true or false about AI. After school, there was a videos session, held two weeks later, which were presented at the Firs Show Videos on Infant Feeding in the auditorium of the City Hall of Macaé. A total of 92 CHA participated in the training, but 89 (97%) answered the test. In the questions about breastfeeding in pre-test met about 90% correct answers, and the post-test, 97%. For questions about complementary feeding, in the pretest, met between 45 and 95% correct. At post-test, between 91 and 96% answered correctly. We conclude that knowledge about breastfeeding is consolidated. Complementary feeding is an issue that should be worked with more emphasis on training of CHA.
Keywords: Breastfeeding; Complementery Feeding; Permanent Education.